MERCHANTS AND OBSERVERS. THE DUTCH REPUBLIC'S COMMERCIAL INTERESTS IN SPAIN AND THE MERCHANT COMMUNITY IN CADIZ IN THE EIGHTEENTH CENTURY.. - Solana, Ana Crespo (Dieciocho: Hispanic Enlightenment)
The external relations of the United Provinces, especially those with the Hispanic Monarchy after 1713, are not very well known. The Provinces are described in some works merely as a secondary power, partly eclipsed by the growth of Great Britain, yet it is possible to detect a certain influence of the Dutch Republic as a mediator in the diplomatic relations between Spain, England and France. This text offers an overview of the role played by the Dutch in this complex international diplomatic context, its socio-political background and the Dutch ideological stance regarding the general evolution of European balance throughout the XVIII century. Emphasis is placed on the analysis of the impact that certain domestic situations, i.e. political changes, the establishment of the so-called "Republic of Regents" or "second era without a Stadhouder" (1702- 1747), had on the relationship with Spain during the first half of the eighteenth century. Further issues will be dealt with, such as the important role played by the Dutch merchant community in Cadia, which had a great influence on the appreciation of Spain by its former enemy and newly found possible collaborator. Dutch, Spanish or English archives have been used as main sources.